PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI CINTA LINGKUNGAN KEPADA PESERTA DIDIK - Ramli Ramli (Universitas Muhammadiyah Surakarta, 2021)
A good madrasah environment is an environment in which is decorated with well-maintained and neatly arranged trees as a natural laboratory for students, and a number of chairs and study tables are neatly arranged. A healthy and good living environment is the human right of every Indonesian citizen, so the planting of environmental love values in madrasah becomes kemestian. This study aims to describe and explain the planting of environmental love values conducted by Islamic Religious Education teachers. This study uses a qualitative approach. The data collection of this research was conducted through interviews, observations, and documentation studies. The results of the study that the planting of the value of environmental love in MTsN 3 Padang City was carried out through the development of madrasah curriculum, including self-development programs, integration in subjects, and madrasah culture. Self-development programs include routine activities, spontaneous activities, conscientiousness, conditioning of hygiene facilities in support of planting the character of environmental love.